A Study on Barriers of Effective Verbal Communication among Higher Secondary Students. - Karbutt, W. Vijay Olga (Journal of Advanced Research in Humanities and Social Sciences; Vol 10 No 2 (2023): Journal of Advanced Research in Humanities and Social Sciences, 2023)
Communication is an essential device for teaching and learning. Communication is a complex process. Communication means a composition of both the verbal and the non-verbal aspects. Communication in the classroom differs from the various formal and non-formal communication settings. The important aspect of classroom communication is to instruct and inform and it happens through verbal communication. Effective verbal communication is necessary for the students to enhance their career and gain confidence. Effective verbal communication is about the words you choose, and how they are heard and interpreted. The capacity to put the words together in a meaningful way to reflect their own thoughts, feelings and opinions helps the students to build their confidence level. An excellence in verbal communication is attained over time and regular practice. Developing vocabulary is a process of acquiring new words to use in their daily life. It helps the students in the Higher Secondary Level to learn the meaning of new words and concepts in various contexts. An ample vocabulary helps the Students to improve themselves. This study helps the students to develop an effective verbal communication. This research helps to find out the level of Barriers, significant difference based on Gender, Location and the type of management among the Higher Secondary School Students. It is found the low level of Barriers of Effective Verbal Communication among the Higher Secondary School Students is 18.18%, high level is 16.69% and moderate level is found to be 64.84%. There exists no significant difference in Gender but there exists significant difference based on their Location and the Type of Management. Communication is the act of sharing information within and across a variety of contexts and cultures. Humans’ communicate in a variety of ways, both verbally and non-verbally. Both the types of communication differ significantly between genders and across cultures.